APPLIED BACHELOR DEGREE: PROSPECTS AND PROBLEMS - Elena A. Lavrent’Eva (Высшее образование в России)
The article dwells on the standard and legal basics of the development of an applied bachelor degree and the advantages of its introduction. The comparative analysis of the model of the state education standard on the academic and applied bachelor degree is made. There are also proposed some measures for implementation of a branch applied bachelor degree. The main statements are the following: 1) an applied baccalaureate is a level of higher education, 2) a bachelor has an opportunity to enter magistracy, 3) education programs of applied baccalaureate should be practice oriented, 4) an applied baccalaureate is a separate field in the corresponding training area: it doesn’t require an additional accreditation, 5) an applied baccalaureate has its own title, 6) an applied bachelor gets a qualification according tothe title of the corresponding education program.